Dynamics of CO2 emission under sweet corn (Zea mays Saccharata) cultivation at ultisol applied with compost - Yulnafatmawita; Suwita Vanessa Putri; Rasyidin Azwar (BIO Web of Conferences)
One source of atmospheric carbon dioxide (CO2) comes from agricultural activities, especially crop cultivation. This research was aimed to measure the amount of CO2 emitted from Ultisol treated with compost during the cultivation of sweet corn. This research was a field experiment with 5 doses of compost (0, 5, 10, 15, and 20 T/ha) and 3 replications. The experimental units were allocated in the field according to a randomized block design (RBD). CO2 emission was measured 4 times (initial, after compost application, maximum vegetative growth, and after harvest). The results showed that there were no significant differences in CO2 emissions between experimental plots before compost application (at initial). However, CO2 emissions were significantly different among treatments after compost application, at maximum vegetative growth, and after harvest. At the three measurements, CO2 emissions increased by increasing doses of compost applied. In addition, laboratory analysis showed that the Ultisol at the research site had a clay texture (53.7% clay particles), low organic carbon (0.77%), and pH (5.21), high bulk density (1.14 Mg m-3), and low total soil pore (56.31%). Although CO2 emissions from the soil surface increased with increasing compost dosage, soil characteristics improved, and crop production increased.